Pemberian Pendidikan Kesehatan Untuk Meningkatkan Pengetahuan Remaja Tentang Penyalahgunaan Napza - Welly; Edo Gusdiansyah (Universitas Alifah Padang, 2024)
people. Drug users no longer see age, even those aged 10 years to the elderly consume a lot of drugs, the types used are methamphetamine, marijuana, glue, amethyst, and drugs. The factors that cause drug users are the first social environmental factors such as curiosity motives, opportunities due to parents busy with their respective activities and lack of affection or as a result of broken homes, facilities and infrastructure, the second is personality such as low self-esteem, feelings of inferiority in society and the environment, the third is emotional and mental such as a person's mental weakness will be more easily influenced towards use (Lisa, 2013). The impact caused as a result of drug use has proven to be very detrimental which can be viewed from all aspects such as medical, social, legal, economic and security. Even if there is no effective and sustainable prevention, it can result in the nation losing its generation (Lisa, 2013).one of the therapies given to patients using drugs is counseling therapy, supportive psychotherapy. The purpose of this community service is to increase adolescents' knowledge of drug use history in the Kuranji Health Center Working Area. This community service method uses the counseling method of providing health education to increase adolescents' knowledge.